2023
DOI: 10.1177/23779608231160463
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Coping Strategies, Compassion Satisfaction, and Compassion Fatigue During the COVID-19 Pandemic

Abstract: Introduction The rapid spread of COVID-19 poses a significant threat to nurses’ lives and health, resulting in varying degrees of mental distress. Nurses may experience compassion fatigue, and their professional quality of life and satisfaction may suffer as a result. Their coping mechanisms may vary as well, influencing their compassionate and safe care. Objectives The study's objectives are to explore levels of compassion satisfaction and fatigue among nurses and identify their coping strategies. Further, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Also, the study showed that the participants’ coping behavior was moderate. This was supported by the Abou Hashish and Ghanem Atalla’s (2023) study. The study showed nurses have a moderate use of coping strategies (2.13 ± 0.35).…”
Section: Discussionsupporting
confidence: 59%
“…Also, the study showed that the participants’ coping behavior was moderate. This was supported by the Abou Hashish and Ghanem Atalla’s (2023) study. The study showed nurses have a moderate use of coping strategies (2.13 ± 0.35).…”
Section: Discussionsupporting
confidence: 59%
“…In this respect, we believe that all power bases and influence tactics are distinct and important, and we suggest that no single strategy is all beneficial in influencing nurses. Like previous research, we thought nurse managers should be smart and skillful to use the different leadership and influential strategies according to the context and nurses' variables (Abou Hashish et al, 2015; Abou Hashish & Atalla, 2023).…”
Section: Discussionmentioning
confidence: 65%
“…beneficial in influencing nurses. Like previous research, we thought nurse managers should be smart and skillful to use the different leadership and influential strategies according to the context and nurses' variables (Abou Hashish et al, 2015;Abou Hashish & Atalla, 2023).…”
Section: Ta B L Ementioning
confidence: 68%
See 1 more Smart Citation
“…Nursing is a career that stands out for its compassionate amenities and human-centeredness. Only nurses interact with patients and their families by specific values [ 27 ]. This suggests that healthcare organizations should prioritize creating a supportive culture that values continuous learning and skill development.…”
Section: Discussionmentioning
confidence: 99%